Perceptions of mental health and perceived barriers to mental health help-seeking amongst refugees: A systematic review. (February 2020) - Byrow, Yulisha; Pajak, Rosanna; Specker, Philippa; Nickerson, Angela
Abstract: Despite elevated rates of psychological disorders amongst individuals from a refugee background, levels of mental health help-seeking in these populations are low. There is an urgent need to understand the key barriers that prevent refugees and asylum-seekers from accessing help for psychological symptoms. This review synthesises literature examining perceptions of mental health and barriers to mental health help-seeking in individuals from a refugee background. Our analysis, which complies with PRISMA reporting guidelines, identified 62 relevant studies. Data extraction and thematic analytic techniques were used to synthesise findings from quantitative ( n = 26) and qualitative ( n = 40) studies. We found that the salient barriers to help-seeking were: (a) cultural barriers, including mental health stigma and knowledge of dominant models of mental health; (b) structural barriers, including financial strain, language proficiency, unstable accommodation, and a lack of understanding of how to access services, and (c) barriers specific to the refugee experience, including immigration status, a lack of trust in authority figures and concerns about confidentiality. We discuss and contextualise these key themes and consider how these findings can inform the development of policies and programs to increase treatment uptake and ultimately reduce the mental health burden amongst refugees and asylum-seekers. Highlights: Mental health stigma was a cultural barrier to help-seeking. Mental health literacy was a cultural barrier to help-seeking. Financial strain, language ability and unstable housing were structural barriers. A lack of understanding of how to access services was a structural barrier. Immigration status and a lack of trust are barriers relevant for refugees.